SiOC films on C/C composite prepared by chemical vapor deposition with hexamethyldisilazane precursor. Issue 14 (15th July 2022) - Wu, Xiumei; Yu, Shu; Li, Yunping
Abstract: Silicon oxycarbide (SiOC) films on C/C composite substrate were prepared by isothermal chemical vapor deposition (CVD) with hexamethyldisilazane (HMDSN) as precursor. The deposition rate, microstructure, composition and mechanical properties of films prepared at deposition temperature ranging from 1300 K to 1576 K were investigated in details. With increasing deposition temperature, deposition rate increased gradually and reached a maximum value of 42.9 μm/h at 1513 K and then decreased; concurrently, the surface morphology of SiOC film changed from a smooth-dense to a coarse cauliflower, and then into a needle-like granular morphology. The SiOC films were composed of dominant SiC and a few other phases at all temperatures. In addition, the contents of oxygen-enriched units SiO3 C and SiO2 increased with deposition temperature due to redistribution reaction of Si –O and Si –C bonds and oxidation. SiOC films prepared at 1373 K showed the highest hardness and elastic modulus for 28.8 GPa and 234.2 GPa, respectively. SiOC films also contained small amounts of Si3 N4 and SiCN at all conditions.